Challenges for Libraries in Difficult Economic Times: Evidence from the UK - Jubb, Michael (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
The last decade has been a period of unprecedented change for university libraries. The rapid growth in numbers of students and staff across the university sector has been accompanied by the move to a substantially digital environment with some fundamental changes in how libraries and their users operate. During this period, most university libraries have seen continued growth in their budgets in real terms, but libraries now face a period in which they will have to cope with continued rapid, perhaps transformational, change, accompanied by reductions in their budgets. This paper is based on evidence gathered and analysed by the Research Information Network on the financial position of university libraries in the UK, and how they are dealing with the prospect of cuts. It highlights two related challenges for libraries: developing and enhancing relationships with their users, and developing new services to maximise their value to users.